Application of Ethnopedagogy and Multicultural Values in Subjects through Project Based Learning Methods - Denada Sihite; Achmad Hufad; Siti Nurbayani (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2022)
As a nation that has cultural diversity, cultural differences can be likened to a coin that has two sides. These differences can be strengths or weaknesses. It becomes a strength if these differences make people become integrated with one another or cause conflict due to existing differences. Education is one way to strengthen unity in the midst of differences and minimize conflicts due to existing differences. Through learning that applies ethnopedagogical and multicultural values that are integrated into subjects at school, it is expected to increase awareness about the importance of knowledge about one's own culture and tolerance for other cultures in a multicultural society. Through the project base learning method, students are expected to be able to explore and understand cultural diversity more deeply. Using data collection techniques, the literature study discusses (1) ethnopedagogy in education, (2) Multiculturalism in education, (3) Integration of ethnopedagogical and multicultural values in subjects, and (4) Application of ethnopedagogical and multicultural values through learning models project based learning